IMPLEMENTATION OF AN AUTOMATIC LPGGAS DETECTION AND ALERT SYSTEM - Dr. B. Mouli Chandra; CH. Ajitha; O. Pavan Kumar; B. Abhishek; T. Venkata Sivamani; CH. Mamatha, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2019)
Gas leakage is a major problem with industrial sector and residential premises. The safety work environment is important for every worker in the industries, hotels, restaurants etc. and important to create a safer workplace. Gas accidents are vital issues for all areas of life where precautions are very important. One of the preventive methods to stop accident associated with the gas leakage is to install gas leakage detection kit at vulnerable places. The aim of this project is to present such a design that can automatically detect, stop and alert gas leakage in vulnerable premises. Therefore an implementation of an automatic LPG gas detection and alert system is proposed in our project. Proposed design can help us to avoid Gasleakage kind of problem in our daily life. The aimof this project is to monitor for liquid petroleum gas (LPG) leakage to avoid fire accidents providing safety feature where security has been an important issue. The system detects the leakageof the LPG using gas sensor and alerts the consumer about the gas leakage by sending SMS.